Nasal food challenge with hen's egg white allergen - Edyta Krzych-Fałta; Andrzej Namysłowski; Sławomir Białek; Monika E. Czerwińska; Konrad Furmańczyk; Aleksandra Tylewicz; Adam Sybilski; Bolesław Samoliński; Oksana Wojas (Allergy, Asthma & Clinical Immunology)
Abstract Background Nasal allergen provocation tests are an important part of the diagnostics of allergic diseases triggered by environmental factors. Recently, increased attention has been paid to the potential use of this method in the diagnosis of food allergy. The objective of the study was to evaluate the usefulness of the nasal allergen provocation test in a group of subjects allergic to hen's egg white allergens. Methods The material consisted of a group of 57 subjects (32 subjects with hen's egg white allergy and 25 healthy controls). The method consisted in a nasal allergen provocation test carried out with the use of hen's egg white allergen and assessed using the visual analog scale and optical rhinometry as well as by determination of sIgE and tryptase levels in nasal lavage fluid. Results Subjective nasal symptoms and objective evaluations following the application of 100 µg of hen's egg white allergen revealed a moderately positive nasal mucosal response in optical rhinometry tests (ΔE = 0.34 OD). Conclusions Nasal food challenge with hen's egg white allergen is a good diagnostic alternative in the group of food allergy patients. Due to the insufficient number of studies carried out so far, further attempts at standardization of the method are required.